1991
DOI: 10.1111/j.1365-2125.1991.tb03878.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and tumour concentrations of platinum in hypoalbuminaemic patients after treatment with cisplatin for cancer of the head and neck.

Abstract: 1 Platinum concentrations in the tumour reached a peak of 3.8 ± 1.5 pLg g-1 wet weight tissue at the end of an 8 h intravenous infusion of cisplatin. The tumour concentrations of platinum were higher than the corresponding plasma concentrations (2.5 ± 0.9 ,g ml-') and declined more slowly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
1
15
0
3
Order By: Relevance
“…DeSimone et al (1987) reported biphasic kinetics of platinum in nine patients with a (t',2,z) of 19.5 to 24.9 h. In this study the terminal half-life in one patient (PM, Figure 1) was about 250 h, although samples were not taken over a long enough period in the other to allow an accurate assessment. The terminal half-lives found by DeSimone et al (1987) are shorter than would be expected from the known kinetics of platinum after conventional cisplatin and probably result from the collection of samples being made over too short a period (Holding et al, 1991) as illustrated by patient AR in this study (Figure 1). …”
Section: Plasma Platinum Concentrationsmentioning
confidence: 59%
See 4 more Smart Citations
“…DeSimone et al (1987) reported biphasic kinetics of platinum in nine patients with a (t',2,z) of 19.5 to 24.9 h. In this study the terminal half-life in one patient (PM, Figure 1) was about 250 h, although samples were not taken over a long enough period in the other to allow an accurate assessment. The terminal half-lives found by DeSimone et al (1987) are shorter than would be expected from the known kinetics of platinum after conventional cisplatin and probably result from the collection of samples being made over too short a period (Holding et al, 1991) as illustrated by patient AR in this study (Figure 1). …”
Section: Plasma Platinum Concentrationsmentioning
confidence: 59%
“…We have previously shown that the median concentration of platinum in tumour biopsies after conventional cisplatin therapy was 3.4 j±g g-1 (Holding et al, 1991) and in all samples measured here the concentration found was greater than this.…”
Section: Tumour Concentrations Ofplatinummentioning
confidence: 86%
See 3 more Smart Citations